DISTRIBUTING SERVICES THROUGH THE CLOUD INFRASTRUCTURE: THE CASE OF A NORWEGIAN SOFTWARE FIRM - Ritter, Christian Simon (AoIR Selected Papers of Internet Research, 2018)
This paper examines how professional practices of software developers forge global assemblages in the oil and gas industry by shedding light on the implementation of cloud technologies within a Norwegian-based digital service company. Delivering digital solutions to oil and gas extracting corporations, this company primarily develops proprietary software providing engineers with business intelligence dashboards that assist in managing the assets involved in the extraction of resources. This extended case study seeks to gain a better understanding of the materialities emerging in cloud environments by illuminating transnational divisions of labor within global assemblages. Committed to a holistic contextualization, this mixed-method investigation is primarily based on ethnographic fieldwork, including participation in industry events and a three-month secondment in a small-scale digital service company. Drawing from a materialistic approach to internet technologies, the study provides a comprehensive account of the digital service company since its founding in 2001. Based on evidence from industry events and a long-term immersion in the working lives of software developers, I suggest that the implementation of cloud technologies in the oil and gas industry prompted new digital divisions of labor and replaced the physical travel of professionals with a remote control system facilitating an enhanced circulation of data. The findings of this investigation imply that cloud computing continues to restructure the global economy and accelerates the migration of data through internet technologies.